1987
DOI: 10.1055/s-2008-1025669
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Threshold in Various Groups of Highly Trained Athletes

Abstract: The ventilatory threshold (VT) was determined on a treadmill in highly trained male marathon, male and female long-distance, young male long-distance, adult male and female and young female middle-distance runners, modern pentathlonists, adult canoeists of both sexes, young male canoeists and football players, and on a bicycle ergometer in table tennis players, water slalom paddlers, young female canoeists rowers, and ice hockey players. Young female canoeists were also examined on the paddling ergometer and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3
6

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 12 publications
4
33
3
6
Order By: Relevance
“…His moderately trained college players had a threshold value of 70.5% of maximal oxygen uptake, which is somewhat lower than the values reported by several other investigators. The adult players in our older study (Bunc et al, 1987) had a % VO2max value of 80.5%. Rhodes et al (1986) found the same value of %VO2max in the Canadian Olympic Team and considered it to be "remarkably high for anaerobically trained athletes".…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…His moderately trained college players had a threshold value of 70.5% of maximal oxygen uptake, which is somewhat lower than the values reported by several other investigators. The adult players in our older study (Bunc et al, 1987) had a % VO2max value of 80.5%. Rhodes et al (1986) found the same value of %VO2max in the Canadian Olympic Team and considered it to be "remarkably high for anaerobically trained athletes".…”
Section: Discussionmentioning
confidence: 74%
“…Metabolic adaptation, which can be indirectly characterized as the ability to utilize effective the functional capacity of the organism during a prolonged period, can be estimated as the percentage of maximal functional variables (mainly maximal oxygen uptake) at VT (Bunc et al, 1987). In untrained subjects, % VO2max.kg -1 is in the range of 50%-70% of maximal oxygen uptake; in trained subjects, values are in the range of 80%-90% of VO2max (Bunc et al, 1987;Wilmore and Costill, 1994) The higher the level of adaptation to physical activity, the higher the values of %VO2max at the VT level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations